Coexistence of T-Cell Lymphoblastic Lymphoma and Ichthyosis Vulgaris: A Case Report - Şule Çalışkan Kamış; Begül Yağcı (Case Reports in Oncological Medicine)
Ichthyosis vulgaris (IV) is an inherited disorder characterized by the scaling of the skin. It is caused by mutations in the filaggrin gene. IV is a reactive skin manifestation that may be associated with malignant hematological disease. Its association with neoplastic diseases such as Hodgkin lymphoma, anaplastic large-cell lymphoma, and mycosis fungoides has been reported. T-cell non-Hodgkin lymphoma (T-NHL) with ichthyosis has been rarely reported in the literature. Here, we report a case of T-cell lymphoma with congenital IV caused by a desmoglein 1 (DSG1) gene mutation associated with hyper-IgE syndrome (HIES). A 7-year-old male patient with a diagnosis of congenital IV had a biopsy performed at an external center due to multiple lymphadenopathies, which revealed T-cell lymphoblastic lymphoma. A homozygous variant in the DSG1 gene was detected through whole-exome sequencing. The diagnosis of HIES was confirmed through clinical evaluation, including elevated serum IgE levels and associated symptoms. Skin findings, growth retardation, and HIES overlap with Online Mendelian Inheritance in Man (OMIM) #615508, and parental carrier status was confirmed. The association between ichthyosis and lymphoma was determined based on the presence of lymphoma in a patient with congenital ichthyosis and the identification of a genetic mutation in DSG1. In conclusion, the coexistence of lymphoma and IV is rare. The mechanisms of their formation are different, and they can occur independently. Rare genetic syndromes or inherited diseases can cause different health problems, such as lymphoma and ichthyosis, to occur together.